Short divalent ethacrynic amides as pro-inhibitors of glutathione S-transferase isozyme Mu and potent sensitisers of cisplatin-resistant ovarian cancers. (31st December 2022) - Xu, Bangtian; Tong, Tingting; Wang, Xin; Liu, Fang; Zhang, Xiang; Hu, Xiaolei; Li, Xinpeng; Yang, Xiaolan; Liao, Fei
Abstract: The linking of ethacrynic acid with ethylenediamine and 1, 4-butanediamine gave EDEA and BDEA, respectively, as membrane-permeable divalent pro-inhibitors of glutathione S -transferase (GST). Their divalent glutathione conjugates showed subnanomolar inhibition and divalence-binding to GSTmu (GSTM) (PDB: 5HWL) at ∼0.35 min −1 . In cisplatin-resistant SK-OV-3, COC1, SGC7901 and A549 cells, GSTM activities probed by 15 nM BDEA or EDEA revealed 5-fold and 1.0-fold increases in cisplatin-resistant SK-OV-3 and COC1 cells, respectively, in comparison with the susceptible parental cells. Being tolerable by HEK293 and LO2 cells, BDEA at 0.2 μM sensitised resistant SK-OV-3 and COC1 cells by ∼3- and ∼5-folds, respectively, released cytochrome c and increased apoptosis; EDEA at 1.0 μM sensitised resistant SK-OV-3 and A549 cells by ∼5- and ∼7-fold, respectively. EDEA at 1.7 μg/g sensitised resistant SK-OV-3 cells to cisplatin at 3.3 μg/g in nude mouse xenograft model. BDEA and EDEA are promising leads for probing cellular GSTM and sensitising cisplatin-resistant ovarian cancers.